Making SMARTer commitments to nutrition action: Global nutrition report guidance note - Fanzo, Jessica; Hawkes, Corinna; Rosettie, Katherine (International Food Policy Research Institute, 2016)
The Global Nutrition Report, an independent accountability mechanism for progress and action on nutrition, calls on all actors to make SMART Commitments to Nutrition Action—that is, commitments that are specific, measurable, achievable, relevant, and time bound. Specifically, we call on governments to make SMART Commitments to Nutrition Action to achieve national nutrition targets and to put in place monitoring systems that allow them and others to assess progress. We also call on all actors—governments, international agencies, bilateral agencies, civil society organizations, and businesses—to revise or extend SMART and ambitious commitments as part of the 2016 N4G Rio Summit process. Actors in other sectors should also specify in a SMART manner how commitments in their own sectors can help advance nutrition.